2022
DOI: 10.21203/rs.3.rs-1542332/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigation of the relationship between a healthy lifestyle, self-esteem and subjective vitality of the elderly in Sirjan in 2020

Abstract: Introduction: This study was conducted aimed to determine the relationship between a healthy lifestyle, self-esteem and subjective vitality of the elderly in Sirjan in 2020.Method: In this descriptive-analytical study, 200 elderly people aged 60 years and older were selected from comprehensive health centers in Sirjan by two-stage random sampling method. The data were collected using validated Healthy Lifestyle Questionnaire among Iranian Elderly, Rosenberg Self-Esteem Scale and validated Subjective Vitality S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…Therefore, an individual with greater vitality experiences increased motivation to conduct purposeful activities [38] and effectively deal with uncertain and stressful situations [39]. Research has revealed that subjective vitality is an important component of self-esteem, life skills, and satisfaction with life, which ultimately leads to increased well-being [40].…”
Section: The Mediating Role Of Subjective Vitalitymentioning
confidence: 99%
“…Therefore, an individual with greater vitality experiences increased motivation to conduct purposeful activities [38] and effectively deal with uncertain and stressful situations [39]. Research has revealed that subjective vitality is an important component of self-esteem, life skills, and satisfaction with life, which ultimately leads to increased well-being [40].…”
Section: The Mediating Role Of Subjective Vitalitymentioning
confidence: 99%
“…Tis article is a part of the master's thesis of Mrs. Parniya Abolghaseminejad, which was implemented at Kerman University of Medical Sciences (A). A preprint has previously been published (Abolghaseminejad P., Borhaninejad V., Khanjani N., Saber M., and Alizadeh D., 2022) [68].…”
Section: Data Availabilitymentioning
confidence: 99%